Um gabinete de curiosidades: Bad Godots e a ciência da mente de Lucky - Gontarski, Stanley (Dramaturgias, 2023)
One of the leading experts on Samuel Beckett, Professor Stanley Gontarski, from Florida State University, discusses the relationship between art and science based on Beckett’s dramatic experiments, especially Waiting for Godot.